PENERAPAN PENDIDIKAN KARAKTER PADA SISWA-SISWI PERGURUAN SILAT WALET PUTI KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Pergianti, Ella; Zahirman, Zahirman; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the issue of the importance of discipline in pencak silat which must be applied by each student. Based on the results of observations (preliminary studies) conducted by researchers at the Silet Puti Silat secretariat / office, students who participated in pencak silat activities had not optimally applied the discipline character well. This is based on interviews with the secretariat / office trainer, that in general there are still many students who are undisciplined, such as arriving late at the training schedule, not in uniform with the reason of forgetting, and there are some students who are not mandated when trusted by parents to pay for training / monthly fees to the coach, but the student does not pay. This proves that students in the Swiftlet Sili College do not yet have a good discipline character. This type of research used in this research is quantitative descriptive research type and the method used is a survey method. The population in this study were 180 students of Swallow Silat College students. The author takes a sample of 22% of the population. Then obtained a sample size of 40 samples. Data collection techniques with questionnaires and interviews. Data analysis uses percentage formulas. Based on the results of research from chapter IV above, it can be concluded that: Not yet well-implemented discipline based on the rules and regulations applied to students of Swallow Silat College in Peranap District. This can be seen from the results of the study which stated that only 50.8% or half of all students who answered "never" and the answer proves that the application of discipline character education in students of Swallow Silat College can be categorized as "Pretty Good".Key Words: Character Education, Walet Puti Silat College